Science under siege : how to fight the five most powerful forces that threaten our world - Mann, Michael E., 1965-; Hotez, Peter J. (PublicAffairs, 2025)
"From pandemics to the climate crisis, humanity faces tougher challenges than ever. But our efforts to effectively tackle these existential crises are now hampered by a common threat: politically and ideologically motivated opposition to science. Michael E. Mann and Peter J. Hotez have spent the last twenty years on the front lines of the battle to convey accurate, reliable, and trustworthy information about science in the face of determined and nihilistic opposition. They reveal the five main forces threatening science: plutocrats, pros, petrostates, phonies, and the press. Armed with the information in this book, we can be empowered to promote scientific truths, shine light on channels of dark money, dismantle the corporations poisoning the planet, and ultimately avert disaster"--